From Maritime Monopoly to Agrarian Control: Colonial Expansion and the Formation of Modern Indonesian Agrarian Structures - Yuni Nur Anggraeni; Rezza Fauzi Muhammad Fahmi; Denisha Luthfiyah Hermawan; Fakhraini ‘Afi Mufidah (Universitas Galuh, 2026)
This article examines how colonial maritime expansion shaped the formation of modern agrarian structures in Indonesia between the sixteenth and early twentieth centuries. Existing historiography—including works by Van Niel (1992) on the Cultivation System, Elson (1994) on peasant Java, and Booth (1998) on colonial economic policies—has largely treated maritime colonialism and agrarian transformation as separate processes. This study argues that colonial control over maritime trade routes functioned as a central mechanism for restructuring agrarian relations, land ownership, and commodity production in the Indonesian archipelago. Using the historical method through literature review and published archival studies, the article demonstrates that the dominance of the Portuguese, the Dutch VOC, and the Dutch East Indies government integrated local agrarian regions into the global capitalist economy through monopolistic trade networks and export-oriented agricultural policies, including the Cultivation System (1830) and the Agrarian Law of 1870. The study contributes to Indonesian colonial historiography by highlighting the interconnected causal relationship between maritime power and agrarian restructuring, showing that modern agrarian inequalities in Indonesia cannot be separated from colonial maritime domination.